PENDIDIKAN AKHLAK DALAM PENCAPAIAN ILMU MANFAAT - Mihmidaty Ya’cub (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2022)
This study aims to describe and analyze moral education in the achievement of useful knowledge to develop ethical concepts in the field of education and as an effort to form the next generation of the nation that has ethics in accordance with educational goals. This study uses a qualitative descriptive approach and the type of research used is library research. The data collection technique is looking for data about things or variables in the form of notes, journals, books and so on. Then the data is collected in the form of written records/data. Meanwhile, the data analysis used is content analysis. The result of this research is that thebenefits of science can only be achieved if the process of learning science with the teacher and with each other is accompanied by the application of morals. Morals that must be applied by students towards teachers include being obedient to teachers, tawadlu', respecting teachers, being honest and sincere, attending places of study with teachers, maintaining a calm place to study, being patient with teachers' attitudes, not opposing, and praying for teachers, being kind. nice to the teacher. The morality of students with each other is also the key to gain beneficial knowledge, among others, namely mutual respect, advising each other, being humble, being kind, not finding fault, forgiving each other, making peace with fellow friends. In order for the teacher's efforts to pass knowledge on to students to succeed, the teacher should apply morals to his students. Among others are conveying knowledge sincerely, loving students, being fair, setting good examples and praying for students.